2022
DOI: 10.7759/cureus.31509
|View full text |Cite
|
Sign up to set email alerts
|

Febrile Seizures in Children: A Review

Abstract: Fever-induced seizures are referred to as febrile seizures (FSs). The most prevalent kind of epilepsy and neurological illness in infants and young children is FS. With a high occurrence seen between the ages of 12 and 18 months, they frequently affect children aged six months to five years. FS is a benign condition that seldom results in brain damage. Nevertheless, they cause stress and emotional anguish for the parents, who may believe that the death of their child is going to occur during the seizure. Latel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
(71 reference statements)
1
4
0
Order By: Relevance
“…Febrile seizures are common in small children and affect 20–50 per 1000 children under 5 years of age 21 . This study found that 21 per 1000 (95% CI 14.4–29.8) reference children had a hospital diagnosis of seizures/epilepsy at ages 0–4 years, indicating good reporting of these diagnoses in our study as not all children with febrile seizures are hospitalised.…”
Section: Discussionsupporting
confidence: 52%
“…Febrile seizures are common in small children and affect 20–50 per 1000 children under 5 years of age 21 . This study found that 21 per 1000 (95% CI 14.4–29.8) reference children had a hospital diagnosis of seizures/epilepsy at ages 0–4 years, indicating good reporting of these diagnoses in our study as not all children with febrile seizures are hospitalised.…”
Section: Discussionsupporting
confidence: 52%
“…В большинстве случаев ФС купируются самостоятельно ещё до госпитализации ребёнка в стационар [1,4,18,46]. ИТ следует начинать, если к моменту прибытия ребёнка в медицинское учреждение судорожные приступы продолжаются [4,47]. Неотложная помощь также потребуется пациентам с длительным фебрильным приступом и ФЭС [48].…”
Section: результаты и обсуждение факторы риска (этиология)unclassified
“…БЗД необходимо использовать у детей с частыми приступами ФС или при ФС продолжительностью более 10 минут [52]. В настоящее время препаратами выбора являются диазепам (0,1-0,2 мг/кг) или лоразепам (0,05-0,1 мг/кг), эффективность которых доказана при периодическом введении у детей перорально, ректально, внутривенно или интраназально [10,12,43,45,47]. В Кокрейновском обзоре 2018 года отмечено, что внутривенное введение лоразепама и диазепама имеет одинаковые показатели прекращения приступов и угнетения дыхания в детском возрасте [50].…”
Section: результаты и обсуждение факторы риска (этиология)unclassified
See 2 more Smart Citations